2020
DOI: 10.34133/2020/8710686
|View full text |Cite
|
Sign up to set email alerts
|

Nanogenerator-Based Self-Powered Sensors for Wearable and Implantable Electronics

Abstract: Wearable and implantable electronics (WIEs) are more and more important and attractive to the public, and they have had positive influences on all aspects of our lives. As a bridge between wearable electronics and their surrounding environment and users, sensors are core components of WIEs and determine the implementation of their many functions. Although the existing sensor technology has evolved to a very advanced level with the rapid progress of advanced materials and nanotechnology, most of them st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 153 publications
(216 reference statements)
0
94
0
Order By: Relevance
“…However, all of these methods still need external power which is hard to miniaturize. Consequently, technologies that harvest energy from the human body or surrounding environment [133] should be further developed and integrated with BP monitoring devices. An alternative way is to use a wrist watch [134,135] for daytime monitoring and a sleeping cushion [127] for overnight use (Fig.…”
Section: B Continuous Blood Pressure Monitoringmentioning
confidence: 99%
“…However, all of these methods still need external power which is hard to miniaturize. Consequently, technologies that harvest energy from the human body or surrounding environment [133] should be further developed and integrated with BP monitoring devices. An alternative way is to use a wrist watch [134,135] for daytime monitoring and a sleeping cushion [127] for overnight use (Fig.…”
Section: B Continuous Blood Pressure Monitoringmentioning
confidence: 99%
“…Sustainable energy harvesting from the environment is always required to meet the increasing energy demand of modern information society [ 1 5 ], especially the burgeoning Internet of Things (IoTs) and bioelectronic devices [ 6 21 ]. As a clean and abundant mechanical source, water flow energy is the most potential candidate in our daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have shown that working at 40 Hz, 3.9 g and a bias of 0.30 , a power density of 1 is harvestable. In summary, the triboelectric harvester appears more suitable for powering small devices, so the space requirement must be limited and therefore the environmental conditions are known 27 . On the other hand, the capacitive harvester appears more suitable for recovery on large structures where pressure and humidity conditions can fluctuate (wave energy recovery 28 for example) and where the size of the harvester (presence of a polarization battery) is not important.…”
Section: Resultsmentioning
confidence: 99%